Arginine vasotocin reduces levels of cooperative behaviour in a cleaner fish - Cardoso, Sónia C. (2015)
Cooperation between unrelated individuals usually involves investments that often mean a decrease in immediate payoffs, but ensure future benefits. Here we investigated the potential role of the neuropeptides Arginine-vasotocin (AVT) and Isotocin (IT) as proximate agents affecting individuals' cooperative levels in the Indo-pacific bluestreak cleanerwrasse Labroides dimidiatus. Their ‘client’ reef fish partners only benefit from interacting if cleaners eat ectoparasites and refrain from gleaning preferred clientmucus. Thus, cleaners must control their impulse to eat according to their preference, and eat less preferred items to maintain ongoing interactions and avoid clients' leaving or punishing. We found that solely the experimental transient higher dosage of AVT led to a decrease of cleaners'willingness to feed against their preference, while IT and AVT antagonists had no significant effects. The sole effect of AVT on cleaner's performance may imply a link between AVT's influence and a potential activation of a stress response. Our results confirm the importance of the AVT/AVP system as an agent affecting levels of cooperation, offering a potential mechanistic pathway for the reported flexible service quality that cleaners provide their clients.